Influence of leadership styles on academician commitment to change: The impact of human resource practices and leader-member exchange - Voon, Mung Ling (Universiti Malaysia Sarawak, (UNIMAS), 2013)
For many organisations, the key to their long-term future lies in their ability to adapt to change. Even so, many organisations face challenges when dealing with the change process. Institutions of higher education are not exempted from such challenges, and when undertaking change initiatives, their success heavily relies on academician capability and commitment-tochange. Despite the importance of successful change initiatives, few studies have examined the linkages between leadership style, commitment-to-change and other contributing factors in the education sector. Therefore, this study specifically addresses these issues by examining the relationship between leadership style and academicians’ commitment-to-change, with the quality of leader-member exchange (LMX) as a moderator, and human resource (HR) practices as a mediator. Data has been collected from sampled academic staff working in 20 Malaysian public universities, using the non-probability purposive sampling technique. From 2000 distributed sets of questionnaires, 470 were returned and useable, resulting in a 24.15 percent response rate. The analysis of this data applied hierarchical multiple regression testing to examine the effects of the moderator and mediator towards the relationship between leadership styles and commitment-to-change. The study findings show transformational, transactional and laissez-faire leadership styles were positively related to commitment-to-change. LMX moderates the relationship between transformational and laissez-faire leadership styles, and commitment-to-change; however, LMX has no moderating effect on the relationship between transactional leadership and v commitment-to-change. Mediation effects were observed with the HR practices dimensions of teamwork and development, and management transparency, on transformational and transactional leadership styles, and academician commitment-to-change. Laissez-faire leadership style and commitment-to-change though, did not exhibit any mediating effect from HR practices. Based on these findings, the study concludes that leadership style, particularly transformational leadership, is an important construct that influences the commitment-tochange of academicians. Overall, the results of this study increase our understanding of the effect of leadership styles on commitment-to-change, as well as the role of LMX and HR practices as moderator and mediator, respectively. Furthermore, the study identifies new leadership and commitment-tochange dimensions, which are unique to the Malaysian context. In addition, this study also provides a significant contribution to university policy makers who are now able to design more effective HR policies and practices, specifically related to teamwork and development, and management transparency, that support higher levels of commitment-to-change. The study further informs university leaders, the head of school, or dean of faculty, that establishing strong, authentic relationships with their subordinates will generate higher levels of academician commitment-to-change.